Context and Implications Document for: On the powers of powerful knowledge. Issue 3 (19th December 2013) - Young, Michael; Muller, Johan
<x xml:space="preserve">Abstract</x> This guide accompanies the following article: Michael Young and Johan Muller, On the powers of powerful knowledge, Review of Education, 10.1002/rev3.3017